Mapping the intersection of e-learning, culture, and tradition: a bibliometric analysis - Yuki, Librilianti Kurnia; Anoegrajekti, Novi; Lustyantie, Ninuk; Abdullah, Khairul Hafezad (Intelektual Pustaka Media Utama, 2025)
The dynamic relationship between e-learning, culture, and tradition has become a compelling field of study due to the ongoing transformation of educational milieus through technology-driven learning. This study aims to identify and analyse patterns in research publications, active institutions, the impact of citations, and keywords on the intricacies of e-learning, culture, and tradition. This study analysed datasets obtained from the Scopus and Web of Science (WoS) databases using the ScientoPy and VOSviewer. The findings demonstrate a significant increase in research output, highlighting the increasing scholarly interest in understanding the intersection of e-learning, culture, and tradition. The prevalence of keywords such as “mobile learning”, “e-learning”, “cultural heritage”, “augmented reality”, and “distance learning” illustrates the dynamic of the educational field stimulated by technological progress and cultural influences. Also, the keywords emphasise exploring novel learning methodologies incorporating digital resources, protecting cultural heritage, and adapting to changing educational environments. This bibliometric analysis contributes to a greater comprehension of how e-learning interacts with cultural and traditional contexts, thereby enriching the discourse surrounding education in a world that is becoming increasingly interconnected.